The Diagnosis and Management of Meralgia Paresthetica: A Narrative Review - Mohammed S. Ahmed; Giustino Varrassi; Despina Hadjiconstanti; Panagiotis Zis (Pain and Therapy)
Abstract Meralgia paresthetica (MP) is a sensory mononeuropathy affecting the lateral femoral cutaneous nerve. Diagnosis is typically made clinically, often utilising multiple diagnostic aids such as imaging and electrophysiology. Upon diagnosis, the management of MP follows the standard ladder, with conservative management first line, followed by steroid injection and finally surgery. Surgery may be neurolysis or neurectomy. A literature review of the PubMed database was performed identifying 594 papers regarding MP or the lateral femoral cutaneous nerve. Following a two-stage screening process and reference searching, 34 articles were included in this review, 11 discussing diagnosis and 23 discussing management. Despite the longstanding knowledge of MP, there remains limited comprehensive research discussing its diagnosis and management. Diagnosis of MP is based on clinical examination, imaging and electrophysiology. There is no obviously superior diagnostic strategy for MP. Once that diagnosis is made, the management strategy is typical of any condition, wherein a patient will move up the intervention ladder. It is apparent that conservative management and steroid injection are both adequate in most patients. Where these strategies fail, surgical options such as decompression, radiofrequency ablation or neurectomy are suitable for the majority of remaining patients. While both neurolysis and neurectomy are described as appropriate strategies, there is a scope for discussion regarding whether one is superior. Other management strategies such as botox, acupuncture and kinesio taping may have some value, but limited research exists on these strategies and further research into these is required.